Biochemical changes in different stages of dendrobium orchid flowers and in vivo flowering via exogenous cytokinin application - Nambiar, Nisha (2013)
Orchids capture the interests of many because of their large diversity,large number of species and varied forms and structures of its flowers. The focus of the present study will be on investigating the biochemical changes that occur in the flowers of four commercially important Dendrobium orchids (D. Angel White, D. Dragon Eye, D. Aredang Green and D. Aredang Blue) at four different developmental stages (buds, halfopened flower, fully bloomed flower and wilted flower). Dendrobium orchids are tropical orchids suitable to be grown under hot and humid environment and are also commercially important as they are mostly used as cut flower. This study would be important towards the understanding of biochemical changes which can occur in a flower prior to flowering and throughout the developmental process of a flower and this information will be useful in the manipulation of flowering induction and the flower longevity. Results from the biochemical characteristics of the selected Dendrobium flowers revealed that protein content increased from the bud stage up to the full bloom stage but reduced thereafter during the wilting stage. Soluble protein content ranged from 9.01 to 12.51 mg/g FW and the total non-soluble protein content was recorded to be ranging from 4.18 to 9.29 mg/g FW. In this study, the relationship between carbohydrate and glucose content throughout the development of flowers from the bud stage to the wilting stage was investigated as well. The total carbohydrate and glucose content was observed to be the highest in half-opened flowers of all four Dendrobium orchid hybrids. The anthocyanin analysis of the Dendrobium flowers showed that the total anthocyanin content was the highest in D. Dragon Eye (deep purple flower) with 27.06 nmol/g FW and the lowest in D. Angel White flowers (white coloured) with only 0.59 nmol/g FW. The results obtained from the various enzyme activities in Dendrobium orchid flowers showed the possible role played by antioxidative enzymes during flowering of orchids can be applied in linking both flowering and senescence process because the enzymes showed different activity level in all the hybrids as their activities were the highest in flowers at wilting stage, showing the essential role played by these enzymes in regulating the senescence process in Dendrobium flowers. In this study also, the role of BAP application in promoting earlier flowering of a selected Dendrobium orchid (D. Angel White) was investigated. The first inflorescence stalk was formed on day 53 in the plants exposed to 200, 250 or 300 mg/L of BAP followed by nine days later for plants sprayed with 150 mg/L of BAP. Plants that were not sprayed with BAP (control) developed approximately 13 leaves per plant, whereas those sprayed with 200 mg/L BAP produced the highest number of leaves followed by plants treated with 150 mg/L of BAP by producing 40.9% and 23.6% more leaves than the control plants. The highest number of flowers per inflorescence (14) was recorded for the plants treated with 200 mg/L BAP followed by plants treated with 150 mg/L BAP which showed 31% less number of flowers than the plants treated with 200 mg/L of BAP. This finding can further be exploited to increase flowering and to promote earlier flowering of other orchids. The quality of flowers obtained were determined based on the total protein content and reducing sugar content in the flowers where the total protein and sugar content increased as the concentrations of BAP applied increased ranging from 24.3 to 61.2 μg /g FW and 1175 to 1220 μg/g FW, respectively. This showed that the quality of the flowers was not affected by the BAP treatment. Furthermore, BAP treatment on D. Angel White at all concentrations also improved the chrorophyll content of its leaves. This study indicates a great potential for speeding up orchid flowering whereby in future, the application of plant growth regulators to plants would be able to stimulate synchronous flowering of orchids which can help Dendrobium orchid types in maintaining a steady position in the floriculture industry.